2014
DOI: 10.1080/10615806.2014.911846
|View full text |Cite
|
Sign up to set email alerts
|

Effects of trait anxiety and situational stress on attentional shifting are buffered by working memory capacity

Abstract: Results are interpreted with respect to ACT and directions for future research are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
55
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(64 citation statements)
references
References 25 publications
8
55
1
Order By: Relevance
“…In addition, our study found that high cognitive scores as assessed by the CAT test predicted performance in the games (higher scores corresponded to higher risk aversion) but did not interact with stress effects on either game. These findings are somehow at odds with emerging evidence indicating that individuals that score higher in tests for executive function are less vulnerable to performance deficits in cognitive tasks resulting from stress or anxiety (Johnson & Gronlund, ; Owens et al ., ; Edwards et al ., ; Thoresen et al ., ).…”
Section: Discussionmentioning
confidence: 98%
“…In addition, our study found that high cognitive scores as assessed by the CAT test predicted performance in the games (higher scores corresponded to higher risk aversion) but did not interact with stress effects on either game. These findings are somehow at odds with emerging evidence indicating that individuals that score higher in tests for executive function are less vulnerable to performance deficits in cognitive tasks resulting from stress or anxiety (Johnson & Gronlund, ; Owens et al ., ; Edwards et al ., ; Thoresen et al ., ).…”
Section: Discussionmentioning
confidence: 98%
“…A sense of safety falls into the realm of emotion, and may pose unnecessary extraneous load to a learning experience and hinder performance similarly to studies previously discussed7 8 45 Learners must be comfortable with their facilitators, and be free to ask questions. Rudolph et al suggest that a simulation briefing should address four major points to create a safe container for the learner.…”
Section: Strategies To Address Extraneous Loadmentioning
confidence: 99%
“…Psychology literature suggests that anxiety during high cognitive demand activities impairs processing efficiency 45. While using simulation as an educational tool, the effects of a crying family member at the bedside interrupting care could create a high stress experience on the learner.…”
Section: Strategies To Address Extraneous Loadmentioning
confidence: 99%
“…Second, some attentional control measurements in these studies (e.g., Stroop task, Booth and Sharma, 2009; highly demanding dual-task, Johnson and Gronlund, 2009; attentional shifting task, Edwards M.S. et al, 2015) confounded attentional control (e.g., the eye movement data) and task performance (e.g., accuracy or reaction time), which might make the indicators less sensitive.…”
Section: Introductionmentioning
confidence: 99%
“…To date, several studies have explored the effects of WMC and anxiety (including TA and SA) on attentional control (Booth and Sharma, 2009; Johnson and Gronlund, 2009; Edwards M.S. et al, 2015; Wood et al, 2015; Wright et al, 2014), but the results of these studies are inconsistent.…”
Section: Introductionmentioning
confidence: 99%